The Best American Newspaper Narratives, Volume 3 - Barry, Dan, 1958-; Reaves, Gayle, 1952- (Book collections on Project MUSE., 2016)
Book is a collection of the 9 top winners of the annual Mayborn Best American Newspaper Narrative Writing Contest.